Search for long-lived particles using displaced jets in proton-proton collisions at root s=13 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2021)
An inclusive search is presented for long-lived particles using displaced jets. The search uses a data sample collected with the CMS detector at the CERN LHC in 2017 and 2018, from proton-proton collisions at a center-of-mass energy of 13 TeV. The results of this search are combined with those of a previous search using a data sample collected with the CMS detector in 2016, yielding a total integrated luminosity of 132 fb(-1). The analysis searches for the distinctive topology of displaced tracks and displaced vertices associated with a dijet system. For a simplified model, where pair-produced long-lived neutral particles decay into quark-antiquark pairs, pair production cross sections larger than 0.07 fb are excluded at 95% confidence level (C.L.) for long-lived particle masses larger than 500 GeV and mean proper decay lengths between 2 and 250 mm. For a model where the standard model-like Higgs boson decays to two long-lived scalar particles that each decays to a quark-antiquark pair, branching fractions larger than 1% are excluded at 95% C.L. for mean proper decay lengths between 1 mm and 340 mm. A group of supersymmetric models with pair-produced long-lived gluinos or top squarks decaying into various final-state topologies containing displaced jets is also tested. Gluino masses up to 2500 GeV and top squark masses up to 1600 GeV are excluded at 95% C.L. for mean proper decay lengths between 3 and 300 mm. The highest lower bounds on mass reach 2600 GeV for long-lived gluinos and 1800 GeV for long-lived top squarks. These are the most stringent limits to date on these models.
Keywords: SUPERSYMMETRY; SQUARK; HIGGS